An explanation for the 18O excess in Noelaerhabdaceae coccolith calcite. - Rickaby, R; Hermoso, M; Minoletti, F; Aloisi, G; Bonifacie, M; McClelland, H; Labourdette, N; Renforth, P; Chaduteau, C (Elsevier, 2016)
Coccoliths have dominated the sedimentary archive in the pelagic environment since the Jurassic. The biominerals produced by the coccolithophores are ideally placed to infer sea surface temperatures from their oxygen isotopic composition, as calcification in this photosynthetic algal group only occurs in the sunlit surface waters. In the present study, we dissect the isotopic mechanisms contributing to the “vital effect”, which overprints the oceanic temperatures recorded in coccolith calcite. Applying the passive diffusion model of carbon acquisition by the marine phytoplankton widely used in biogeochemical and palaeoceanographic studies, our results suggest that the oxygen isotope offsets from inorganic calcite in fast dividing species Emiliania huxleyi and Gephyrocapsa oceanica originates from the legacy of assimilated 18O-rich CO2 that induces transient isotopic disequilibrium to the internal dissolved inorganic carbon (DIC) pool. The extent to which this intracellular isotopic disequilibrium is recorded in coccolith calcite (1.5 to +3 ‰ over a 10 to 25 °C temperature range) is set by the degree of isotopic re-equilibration between CO2 and water molecules before intracellular mineralisation. We show that the extent of re-equilibration is, in turn, set by temperature through both physiological (dynamics of the utilisation of the DIC pool) and thermodynamic (completeness of the re-equilibration of the relative 18O-rich CO2 influx) processes. At the highest temperature, less ambient aqueous CO2 is present for algal growth, and the consequence of carbon limitation is exacerbation of the oxygen isotope vital effect, obliterating the temperature signal. This culture dataset further demonstrates that the vital effect is variable for a given species / morphotype, and depends on the intricate relationship between the environment and the physiology of biomineralising algae.